Billy Summers : a Novel - King, Stephen 1947- (New York : Scribner, 2021)
"When Billy Summers was twelve years old, He shot and killed his mother's boyfriend after he kicked Billy's sister to death. At 17, he enlisted in the army. At 18, he was a sniper in Iraq and involved in the deadly battle to recapture Fallujah. For nearly twenty years, he's worked as a paid assassin. He's a good guy in a bad job, and he wants out. He takes on a very complicated, very lucrative job that he hopes will be his last. He's got a perfect new identity lined up and a scrupulously orchestrated, flawless escape plan. And then something happens that changes everything for Billy. A stranger needs rescuing, and Billy sacrifices the safety of his own perfectly devised new life to offer her protection. And then the two of them-the most compelling and surprising duo in King fiction-set out on one last mission, to rectify the injustices of one extraordinarily evil man"--
Keywords: Assassins -- Fiction; Undercover operations -- Fiction; Good and evil -- Fiction; Revenge -- Fiction; Good and evil -- Fiction; Adventure fiction; Suspense fiction